Enhancing English Language Skills of Upper Secondary Students through Content and Language Integrated Learning - Arun Meadseena; Jiraporn Chano (Journal of Educational Issues, 2024)
The purposes of this research aimed to enhance English language skills of upper secondary students through content and language integrated learning. The research procedures involved three phases as following: the first phase studied fundamental information. The second phase designed and developed the instructional strategies. The third phase implemented instructional model to enhance English language skills through content and language integrated learning. Forty of 11th grade students, second semester of academic year of 2018 selected through cluster random sampling. The assessment tools were a questionnaire, an achievement test, an English language skills test, and a satisfaction questionnaire. The result showed that students improved their listening and speaking skills. Achievement learning from the students is a result that has been achieved by students who obtain listening and speaking skills. At the 0.5 level of statistical significance, Students who were taught using content and language integrated learning outperformed those who were taught using traditional methods. CLIL learning provided students with a high level of learning satisfaction.